The role of miR-29 family members in malignant hematopoiesis - Kollinerova, Sona; Vassanelli, Stefano; Modriansky, Martin (Biomedical papers, 2014)
Aims: MicroRNAs of the miR-29 family members were one of the first microRNAs identified as possible therapeutic agents in malignant hematopoiesis. The aim of our review is to summarize the current state of knowledge on miR-29 family members.Methods: We performed literature searches involving miR-29 family members and their relationship to individual hematological malignancies, namely acute myeloid leukemia (AML), chronic lymphoblastic leukemia (CLL) and chronic myeloid leukemia (CML). We also searched for subgroups of hematological malignancies, e.g. multiple myeloma, that are regarded as members of the acute or chronic types of leukemias.Results: A number of genes appear to be regulated by miR-29 family members in various physiological and pathological situations. In our view regulation of Tcl-1, Mcl-1 and DNA methyltransferases is relevant in case of hematological malignancies, hence these are the focus of this review. miR-29 family members also function during normal T-cell and B-cell development.Conclusion: MiR-29 family members appear to govern some general features in commonly heterogenous hematological malignancies and therefore form a potential target for treatment.
Keywords: microRNA; miR-29; hematopoiesis; leukemia; post-transcriptional regulation